Identification of Heat Waves and Analysis of Their Temporal-Spatial Variations in Iran - Nasibeh Baharvandi; Firouz Mojarrad; Jafar Masompour (تحقیقات کاربردی علوم جغرافیایی)
The heat wave is a long period of warm climate, compared to the expected conditions in a region over a certain period of the year. Heat waves cause mortality, disease and various problems in different fields of transportation, agriculture, production and energy. It is very important to study the changes in spatial and temporal patterns of these waves to understand the causes of the incident and confront them. In the present study, using the "Heat Wave Magnitude Index daily" (HWMId), which takes into account both the intensity and the wavelength of heat, the heat waves of Iran between 1985 and 2015 have been analyzed in terms of spatial and temporal distribution. For this purpose, using the maximum daily temperature data of 44 synoptic stations of the country and on the basis of the threshold of the 90th percentile, the heat waves greater than or equal to three days were identified at each station. After applying the HWMId on the days of each heat wave, the magnitude of each wave was calculated. Then, the average number and magnitude of all waves, as well as the most severe ones, were calculated in annual and seasonal scales and the corresponding maps and charts were drawn up. The results of the study showed that the highest number of heat waves occurs in the western part of the Zagros Mountains and then the Kavir Plain; while the maximum magnitude of heat waves belong to the south-east and central parts of the country. Autumn and then winter season have a high share of the most severe heat waves during the study period; while the spring and summer heat waves are relatively weaker, and are more limited in terms of expansion. The most severe heat waves during the study period have occurred in the winters of 2008 and 2010. The number and magnitude of heat waves in the country is increasing significantly. The largest increase in the number belongs to the summer and the magnitude belongs to the winter.